Low-Hanging Fruit: Leadership, Perceived Prosocial Impact, and Employee Motivation. Issue 9 (29th July 2017) - Bro, Louise Ladegaard; Andersen, Lotte Bøgh; Bøllingtoft, Anne
ABSTRACT: Transformational leadership affects public service motivation, but little is known about the context dependency of this association. If citizen contact and, therefore, relative perceived impacts on others and society differ, the association between transformational leadership and motivation is also expected to differ. Analyzing public employees and their leaders from four organizational contexts, we find that employees have relatively higher perceived impact on others and are more user-oriented in contexts with high citizen contact. The association between transformational leadership and employee motivation also depends on employees' perceived impact, implying that some fruit hangs lower than other when leaders try to increase employee motivation.